Lies, Damned Lies, or Statistics How to Tell the Truth with Statistics - Poritz, Jonathan A. (Open textbook library., 2017)
This is a first draft of a free (as in speech, not as in beer, [Sta02]) (although it is free as in beer as well) textbook for a one-semester, undergraduate statistics course. It was used for Math 156 at Colorado State University–Pueblo in the spring semester of 2017.